Auricular malformation treated by placement of an osseointegrated implant-supported epithesis using telenavigation and model simulation: A case report. Issue 1 (January 2015) - Usuda, Shin; Truppe, Michael; Kaneko, Tsuyoshi; Ogawa, Kaoru; Asoda, Seiji; Hatazawa, Chika; Usuda, Sho; Yamada, Yuka; Ewers, Rolf; Nakagawa, Taneaki; Kawana, Hiromasa
Abstract We report a case of auricular malformation treated by placement of an osseointegrated implant-supported epithesis using telenavigation and model simulation. A 66-year-old male suffering from auricular malformation and atresia auris of his right ear since birth visited our department in October 2006. The patient desired placement of an ear epithesis supported by osseointegrated implants. Computed tomographic (CT) scans were obtained for use in the navigation system as a prerequisite for the telenavigation and the operative plan was designed in consultation with an overseas oral and maxillofacial surgeon having rich experience in telenavigation surgery. We also constructed a preoperative simulation model and a mirror model of the unaffected left ear based on laser lithography to produce successful operation and symmetrical form of a symmetrical ear epithesis as contrast with identical to that on the left side. The osseointegrated implant surgery was carried out under telenavigation guidance. As a result, safe and accurate positioning of the implants was achieved and a symmetrical and elaborate epithesis could be fabricated.